Strategi Pengembangan Pasar Domestik Pertanian dalam Menghadapi Persaingan Global - Djoko Said Damardjati (Iptek Tanaman Pangan, 2011)
Strong and competitive domestic market is a key for facing the world market which is increasingly liberal, open and global. The domestic market structure will change dynamically to adjust the development and to be compatible with the world market. Therefore, the development for better market infrastructure, institutional, human resources, policy and other support facilities should be directed in such a way as to be able to carry out the distribution of goods efficiently that benefits all players, including farmers’ as a producer and consumer. Transformation from farmer producers to farmer suppliers through GAPOKTAN is required. At the distribution and marketing level, there is a need to develop institutional and efficient marketing system through the establishment of the agribusiness terminal (TA) and agribusiness sub-terminal (STA). To build an effective marketing network synergistic cooperation is needed among all agencies and stakeholders, in building and empowering institutional facilities of the existing markets and streamline of critical nodes in the agricultural marketing chains. Traditional markets and modern markets (super market and hypermarket) as the primary goal of marketing of agricultural commodities are objects that need to be fairly regulated. With the very dynamic market developments as demanded by consumers, the traditional market is expected to reorganize themselves into semi-modern interprices in order to remain a good choice for consumers and competitive with modern markets. The development of modern markets both supermarkets and hypermarkets also need to be regulated so that their growth would not to be ‘counter-productive’ with the efforts of building a strong and competitive domestic product market. Competitive domestic market of the local products that compete well with imported products, and the high absorption of the local products is expected to the entry of imported products into the Indonesian market.